Brand placements in video games: How local in‐game experiences influence brand attitudes. Issue 2 (5th December 2022) - Ingendahl, Moritz; Vogel, Tobias; Maedche, Alexander; Wänke, Michaela
Abstract: Brand placements are omnipresent in video games, but their overall effect on brand attitudes is small and varies substantially between studies. The present research takes an evaluative conditioning perspective to explain when and how brand placements in video games influence brand attitudes. In two experiments with a 3D first‐person video game, we show that only brands encountered during positive in‐game experiences benefit from the placement, but not those encountered during negative in‐game experiences. Building on the cognitive processes underlying evaluative conditioning, we also show that brand attitudes largely depend on the memory for the pairing of a brand with positive/negative in‐game experiences. Pairing memory and thus also evaluative conditioning effects increase when players attend to the pairing of brands and positive/negative experiences, for example, when such pairings are a central part of the game's storyline. Overall, our findings show that evaluative conditioning and its cognitive mechanisms can be utilized to explain and predict advertising effects in applied settings, such as brand placements in video games.